Environmental Education and Indigenous Knowledge in New Caledonian Geography Textbooks - Stastny, Angélique; Kowasch, Matthias (Journal of Geography Education, 2023)
This article explores the ways in which Indigenous Ecological Knowledge (IEK) and sustainable development are represented in New Caledonian Geography textbooks and curricula. Our case study shows that state-driven Environmental and Sustainability Education is often linked to implicit neoliberal values and the paradigm of economic growth, and marginalizes Kanak Indigenous knowledge and practices. IEK is rooted in land, sea, and resource governance. It is therefore necessary to think Kanak knowledge beyond current institutional boundaries. We believe that customary principles, values, and ecological knowledge of Kanak cultures should find a rightful place in formal education.
Keywords: Indigenous environmental knowledge, Kanak cultures, Geography teaching, textbooks